Theorising emergent public spheres: negotiating democracy, development, and dissent - Barnett, Clive (University of the Free State, 2014)
This article outlines an analytical framework for investigating the variable formation of public life. It suggests that theoretical accounts of the public sphere and related ideas should be thought of less as normative models to be applied to new contexts, and more as providing questions as to how different values of publicness emerge in new situations. It is suggested that the South African experience of public formation since the 1990s can inform the development of this type of framework, insofar as it challenges some of the normative assumptions built into academic, activist and policy understandings of the form and context of public life. The plurality of values associated with ideas of publicness is elaborated through a discussion of the grammars of public value; the specifically public content of publicness is shown to revolve around ideas of sharing as partaking, and three paradigms of public action are identified. The article concludes by identifying three dimensions around which the investigation and evaluation of emergent public formations might be organised.
Keywords: Public life